All-Optical Single-Longitudinal-Mode Forward Brillouin Microwave Oscillator with an Unbalanced Fiber Mach–Zehnder Interferometer - Xinyue Fang; Wenjun He; Wen Wang; Yi Liu; Yajun You; Qing Yan; Yafei Hou; Zepeng Wu; Lei Yu; Songquan Yan; Mingxing Li; Jian He; et al. (Micromachines)
An all-optical single-longitudinal-mode (SLM) forward Brillouin microwave oscillator (FB-MO) with an unbalanced Fiber Mach–Zehnder interferometer (UF-MZI) for microwave photonics (MWP) generation is proposed and experimentally investigated. UF-MZI consists of an optical coupler (OC), a polarization controller (PC), and two asymmetric length arms with 5 km and 500 m single-mode fibers (SMFs), which implements two unbalanced length feedback rings that are connected to one another. One long-length ring with a forward Brillouin gain cooperates with the other short-length ring to maintain a spectral Vernier effect and improve the effective free spectral range (FSR). By contrast with traditional optoelectronic oscillators (OEOs), this design does not require any photoelectric conversion devices and additional modulation, avoids external electromagnetic interference, and side-mode suppression and linewidth are favorable. Experimental results reveal that the 3-dB linewidth of the all-optical SLM FB-MO with UF-MZI is about 140 Hz. The acoustic-mode and side-mode suppression ratios are 26 dB and 31 dB. Within 60 min of the stability experiment, the power and frequency stability fluctuation were ±1 dB and ±100 Hz. Thanks to its long main ring cavity length, our all-optical SLM FB-MO with UF-MZI maintains good phase-noise performance. The measurement shows that a phase noise as low as −120 dBc/Hz at an offset frequency of 100 kHz is achieved. This SLM MWP generation technology holds great potential for applications in radar monitoring and wireless communication systems.